Hubungan Antara Kepercayaan Pada Pedagang Internet Dan Kepribadian Big Five Dengan Intensi Membeli Pakaian Melalui Internet - Utomo, Genjadid (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
Abstract Internet has become a necessity for any individual or organization. Buying and selling through the Internet (e-commerce) be noteworthy given the potential number of Internet users in Indonesia, however, still there are many problems that can be a risk factor of buying through the internet, especially in the sale of clothing is a basic requirement per person . This study aims to determine the relationship between trust in the internet merchants and big five personality with the intention of buying clothes over the internet. This research on the subject among the students due to the high demand for internet. Regression analysis is a method to uncover the hypothesis in this study, showed that reliance on the internet merchants and big five personality capable of predicting consumer intention to buy clothes over the internet for 32.4% (R2 = 0.324), with a p value of 0.01 (p <0.5), which means significantly. Separately reliance on the internet merchants have a significant relationship with the intention of buying clothes over the internet with a significance level of p 0.000 (p <0.5). While the big five personality consisting of 5 factors, did not show an association with the intention of buying clothes over the internet.Keywords: intention, trust, personality, big five, internet Â